A case of bladder diverticulum simulating ovarian cyst during pregnancy - Rani, Anjali; Matah, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
33 year old female G3P2+0 at 32 weeks of gestation was admitted in labour room with the complain of pain abdomen and difficulty in passing urine. On examination vitals were stable. Abdominal examination there was cystic swelling in suprapubic region extending up to umbilical region. Uterus was 32 week size. Report of USG from peripheral centre showed ovarian cyst. We made a provisional diagnosis of twisted ovarian cyst. Exploratory laparotomy was done there was no ovarian cyst and bladder diverticulum was present. Urologist called and first he aspirated fluid and it was urine. Then while separating the swelling from uterus bladder opened and resected the diverticulum. Bladder was sutured. Abdomen was closed. Patient went into preterm labour and delivered vaginally single live female of 2.1 kg weight. Postoperative period was uneventful. Patient was lost in follow up.